ASYMMETRIC DIMETHYLARGININE - Raharjo, Loo Hariyanto (Universitas Wijaya Kusuma Surabaya, 2010)
Asymmetric dimethylarginine (ADMA) is a naturally occurring chemical found in blood plasma. It is a metabolic by-product of continual protein modification processes in the cytoplasm of all human cells. It is closely related to L-arginine, a conditionally-essential amino acid. ADMA interferes with L-arginine in the production of nitric oxide, a key chemical to endothelial and hence cardiovascular health. ADMAconcentration is elevated in patients with end-stage renal disease (ESRD), in part because it is excretedvia the kidneys.Â